An Organismal Perspective on the Evolution of Insect Societies - Helanterä, Heikki (Frontiers in Ecology and Evolution, 2016)
Insect societies, i.e. the colonies of eusocial ants, bees, wasps and termites, have been likened to multicellular organisms for more than a century. This framework of “superorganisms” has to date largely been used as a mechanistic description of colony functioning, or as an example of an evolutionary transition in individuality. Here I take the superorganismal view a step further, and explore what can potentially be gained if we truly accept insect societies as organisms. I suggest ways to test evolutionary theories about organismal features originally derived for solitary organisms using traits of insect societies as analogies. I explore examples such as evolution of anisogamy, sex allocation and fertilization strategies and life histories, and point out promising directions for comparative work, and potential confounding factors in such analyses, derived from social insect studies.